2010
DOI: 10.1111/j.1574-6968.2009.01884.x
|View full text |Cite
|
Sign up to set email alerts
|

Functional characterization of theglxRdeletion mutant ofCorynebacterium glutamicumATCC 13032: involvement of GlxR in acetate metabolism and carbon catabolite repression

Abstract: Recently, a cyclic AMP receptor protein homologue, GlxR, was reported to bind to the upstream regions of several genes involved in the regulation of diverse physiological processes in Corynebacterium glutamicum. However, the function of GlxR has not yet been explored in C. glutamicum in vivo using a glxR deletion mutant. Therefore, this study examines the role of GlxR as a repressor in glyoxylate bypass and carbon catabolite repression (CCR) using a deletion mutant. The disruption of glxR resulted in a severe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
35
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 35 publications
1
35
0
Order By: Relevance
“…We previously showed that GlxR mediates not only glucose-dependent upregulation of the glycolytic genes gapA and pfk, encoding glyceraldehyde-3-phosphate dehydrogenase and phosphofructokinase, respectively, but also the carbon source-independent upregulation of genes for ATP synthase and cytochrome c oxidase (15). It has also been reported that the glyoxylate pathway genes aceA and aceB, which encode isocitrate lyase and malate synthase, respectively, are negatively regulated by GlxR in the presence of either glucose or acetate (54). These findings indicate that the intracellular cAMP levels and the regulatory roles of GlxR are not necessarily correlated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously showed that GlxR mediates not only glucose-dependent upregulation of the glycolytic genes gapA and pfk, encoding glyceraldehyde-3-phosphate dehydrogenase and phosphofructokinase, respectively, but also the carbon source-independent upregulation of genes for ATP synthase and cytochrome c oxidase (15). It has also been reported that the glyoxylate pathway genes aceA and aceB, which encode isocitrate lyase and malate synthase, respectively, are negatively regulated by GlxR in the presence of either glucose or acetate (54). These findings indicate that the intracellular cAMP levels and the regulatory roles of GlxR are not necessarily correlated.…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of the presumed physiological function of each type of FFL, the coherent FFLs formed with GlxR-RamA and SugR-RamA are predicted to play a role in maintaining gapA expression levels in response to fluctuations in cAMP and sugar phosphate levels, whereas the incoherent FFL composed of RamA-SugR may be involved in a rapid response to physiological and/or environmental changes, which are sensed by RamA. Moreover, the FFLs formed by GlxR and RamA are possibly involved in regulation of other central carbon metabolism genes, i.e., ptsF, gltA, acn, sdhCAB, aceA, and aceB, encoding the fructose uptake phosphotransferase system, citrate synthase, aconitase, succinate dehydrogenase, isocitrate lyase, and malate synthase, respectively (35,38,45,54,(62)(63)(64)(65). Further insights into the biological roles of these complex regulatory connections will be provided by elucidation of the environmental signals to which RamA and RamB respond and how the intracellular cAMP levels are controlled.…”
Section: Discussionmentioning
confidence: 99%
“…In silico analyses have detected more than 200 potential binding sites for GlxR in the C. glutamicum genome, and binding to 72 of the sites has been verified by in vitro binding assays, revealing that the regulon includes genes for carbon metabolism, nitrogen metabolism, respiration, resuscitation, cell wall formation, and cell division (42,43). However, whether GlxR acts as a transcriptional activator or repressor of most of these genes is difficult to evaluate, not only because construction of a glxR deletion mutant is difficult but because any mutant that has been successfully constructed shows severe growth defects (41,49,59,79). The role of GlxR has been assessed only by in vitro binding assays and overexpression studies in vivo (14,32,33,40,49), although GlxRdependent repression of genes involved in the glyoxylate pathway and glutamate uptake system was recently confirmed by experiments using a glxR mutant (59).…”
mentioning
confidence: 99%
“…Therefore, it remains unknown what signal GlxR-cAMP responds to and what regulatory role GlxR-cAMP plays in C. glutamicum. In this context, it should be noted that the cyaB disruptant still has a certain level of intracellular cAMP, as reported in a recent study (Cha et al, 2010), and that the phenotypes of the glxR and cyaB deletion mutants are not comparable (Cha et al, 2010;Park et al, 2010). Further studies on the regulatory mechanism of GlxRcAMP may provide insight into new aspects of the role of cAMP in global genetic regulation in bacteria.…”
Section: Discussionmentioning
confidence: 92%